New series of practical leaflets - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
The Natural Resources Institute of the UK Overseas Development Administration (ODA) has launched a series of technical leaflets which are simple, illustrated guides to processes that have practical application in rural development. The first is...